Horasan ve Maveraünnehir’de İlk İsmâ'îli Faaliyetler - Muzaffer Tan (Dini Araştırmalar, 2015)
Although Khorasan and Transoxiana have an important place in view of Ismaili activities of mission (da‘wa), the studies on the Ismaili activities there have remarkable remained limited in number so far. This is perhaps due the lack of information that will shed light on the first Ismaili activities in the region. However, it is obvious there stil remains a certain gap the needs more studies so that the history of sects in the region and their processes of interaction could be put forth in a sound way. In this connection, this article aims to make an unpretentious contribution to the gap in question